"So Much for Protect and Serve": Queer Male Survivors' Perceptions of Negative Police Experiences. (May 2020) - Meyer, Doug
The author employs a critical queer criminology approach to examine the negative reporting experiences of queer men who have been sexually assaulted. Based on qualitative, in-depth interviews, findings reveal that queer men of color's perceptions differed based on gender expression with those participants who did not describe themselves as feminine or gender-nonconforming expressing surprise that police officers had disparaged their sexuality. Moreover, White participants differed based on age, as younger White queer men expected the police to provide support, whereas their older counterparts were not surprised by the negative police response. These findings have implications for theorizing the intersections of gender and sexuality with race and age, given that results indicate younger White queer men may now increasingly perceive the police as providing protection. In contrast, gender-nonconforming queer men of color described continual profiling experiences based on their gender presentation and their racial identity.